Public participation in local development in the opinion of local governments and social economy entities - Barbara Kryk; Izabela Szamrej-Baran (Economic and Environmental Studies (E&ES), 2019)
The aim of the article is to assess the role and the level of social participation in local development in the light of the opinions of local governments and entities of social economy. In the new paradigm of territorial development, an important role is attributed to the cooperation of local government units with society, considered as a vital factor in local development. This cooperation is determined, among others, by engaging citizens in local matters, including through social economy entities. Local authorities and social economy entities perceive and evaluate this activity in a slightly different way, which is not conducive to the development of cooperation and the region itself. Therefore, it is important to identify these discrepancies in order to take appropriate pro-development measures. The following methods were used in the study: literature analysis, comparative analysis of the results of surveys carried out in the communes of the West Pomeranian Voivodeship and among social economy entities operating in this province (the research was carried out in 2017-2018), inference and plus evaluations. Consequently, they enabled (1) to make a synthetic assessment of the role and the level of social involvement in local development and to indicate differences in its perception by the surveyed entities, as well as (2) to formulate recommendations for improving cooperation between local governments and society and social economy entities.
Keywords: O43; R11; R59; 330; local development; public participation; local self-government